Principals’ Ethical Leadership Perspectives: A Narrative Inquiry - Sherchand, Bipin; Baskota, Prateet; Lawati, Anjali Limbu (Interdisciplinary Issues in Education, 2023)
Everyone's top priority is ethics because it is the foundation of a prosperous society. The educational system is responsible for cultivating, fostering, and strengthening ethical sensibilities in society. Respected as innovators, explorers, and transformers of ethical awareness are educators and principals. Unfortunately, they lack the maturity and confusion necessary to serve as examples. They receive criticism as a result of their various unethical actions. This paper presents stories of school principals from their leadership experiences while drawing on ethical school leadership. The primary goal of this paper is to examine three-dimensional lived experiences: care ethics, justice ethics, and critiques of ethical leadership. We mainly focused on the principals' professional backgrounds, performances, and epistemological perspectives regarding ethical leadership. In-depth interviews from protracted interviews were used to create narratives as part of interpretivist narrative inquiry—four principals specifically chosen from Kathmandu Valley institutional schools. The interpretations were verified by pertinent literature. This study examined how ethical leadership promotes fairness in society and schools by valuing individuals. Crossing the structural line to include and empower the followers also takes courage. This research clarified the nature of the school leadership phenomenon so that concerned authorities could enhance matters. Additionally, it might direct readers toward moral principles that could serve as a fundamental tenet.